Problem Kristologi dan Istilah-istilah Kunci - Putri, Amanda Gresella; Hanti Hanti; Lira Oktoratilova; Theresia Anjelie (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Christology is a branch of theology that discusses the person and work of Jesus Christ, but understanding it is often hindered by theological and terminological problems. This article aims to explain the problems of Christology and the related key terms, as well as to elaborate their application in Christian Religious Education. The method used is qualitative research with a library research approach, referring to theological books, church council results, and relevant journals. Data analysis was conducted using content analysis and a hermeneutic approach. The findings indicate that the main problem of Christology is the tension between the divinity and humanity of Jesus, which gave rise to heresies such as Arianism, Nestorianism, and Monophysitism. The church responded through ecumenical councils by formulating key terms such as homoousios, hypostasis, kenosis, communicatio idiomatum, and unio hypostatica. Understanding Christology has important implications for Christian Religious Education, namely strengthening the foundation of faith, experiencing faith more meaningfully, building Christ-centered spirituality, and equipping Christian Religious Education teachers to correctly teach the Christian faith amidst the complex flow of digital information.